2003
DOI: 10.1097/00006565-200302000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Nonurgent pediatric emergency department visits: Care-seeking behavior and parental knowledge of insurance

Abstract: OBJECTIVES The goals of this study were to describe the factors associated with utilization of emergency services for nonurgent illnesses by insured children in a pediatric emergency department (PED) and to assess parental knowledge of their insurance and its influence on care-seeking behaviors. METHODS We conducted a prospective, descriptive survey of parents of insured children evaluated for nonurgent illnesses in an urban PED. RESULTS A total of 251 surveys were completed. The primary reason chosen by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 20 publications
1
51
0
1
Order By: Relevance
“…[10] In addition to these points, multiple studies have shown that many patients view the ED as faster and more convenient. [4,5,7,11] In Kentucky, one survey revealed that patients in fact would prefer to see their usual primary care physicians, but nearly half would "seek care elsewhere" if they could not be seen the same day. [12] Our study did not show a statistically significant difference in patient perceptions regarding convenience of ED versus primary care providers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[10] In addition to these points, multiple studies have shown that many patients view the ED as faster and more convenient. [4,5,7,11] In Kentucky, one survey revealed that patients in fact would prefer to see their usual primary care physicians, but nearly half would "seek care elsewhere" if they could not be seen the same day. [12] Our study did not show a statistically significant difference in patient perceptions regarding convenience of ED versus primary care providers.…”
Section: Discussionmentioning
confidence: 99%
“…that though many patients admittedly do not attempt to make contact with their primary care physicians, of those that do, a vast majority are directed to go to the ED. [2,4,13] An United Kingdom study found that patients whom self-referred themselves to the ED had the same incidence of non-emergent complaints as those patients referred by their primary care providers. [14] In our research, the self-referral versus primary care referral rates showed more patients not contacting their primary care physicians before visiting the ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations